2014
DOI: 10.1111/aogs.12470
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of birthweight by measurement of fetal thigh soft‐tissue thickness improves the detection of macrosomic fetuses

Abstract: The accuracy of sonographic estimation of birthweight in suspected macrosomic fetuses is compromised by the imprecision of the biometrical measurements. This prospective study evaluated the performance of an equation based on linear measurement of the soft tissue above the external side of the fetal femur. The performance of this algorithm was compared with two classical algorithms. Sonographic measurements were taken within 48 h before of delivery. Sixty-two patients with fetuses with suspected macrosomia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Moreover, it includes a measurement of soft tissue, thought to be of great value to evaluate fetal growth deviations as it involves adipose tissue plus lean mass. [15][16][17][18][19] Although previous studies have recently shown the benefits of these linear measurements, particularly mid-thigh STT, 15,[17][18][19][20][21] the advantage of this formula has yet to be established in order it can be routinely used, i.e. in the labor ward, where it could be most useful.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it includes a measurement of soft tissue, thought to be of great value to evaluate fetal growth deviations as it involves adipose tissue plus lean mass. [15][16][17][18][19] Although previous studies have recently shown the benefits of these linear measurements, particularly mid-thigh STT, 15,[17][18][19][20][21] the advantage of this formula has yet to be established in order it can be routinely used, i.e. in the labor ward, where it could be most useful.…”
Section: Introductionmentioning
confidence: 99%
“…Another parameter, FSTT, was strongly correlated with fetal AC and BW according to Scioscia et al The new formula derived by adding FSTT showed higher efficacy than the Shepard and Hadlock formulas. 13 The utility of the new parameter was found by others to be valuable in macrosomia. 24 However, Chauhan et al did not confirm the correlation of FSTT as a predictor of high BW.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, no significant correlation was found between HSTT and FW estimation and BW. Another parameter, FSTT, was strongly correlated with fetal AC and BW according to Scioscia et al The new formula derived by adding FSTT showed higher efficacy than the Shepard and Hadlock formulas 13 . The utility of the new parameter was found by others to be valuable in macrosomia 24 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations